MANAGEMENT OF COMMINUTED FRACTURES OF THE OLECRANON BY TENSION BAND WIRING - Sultan, Shahid; Khan, Alam Zeb (Journal of Ayub Medical College Abbottabad, 2003)
Background: Open reduction and rigid internal fixation has become the generally accepted method of treatment for displaced fractures of the olecranon in order to allow early mobilisation and to prevent contracture of the elbow. Comminuted fractures of olecranon are unstable, therefore, bone graft and tension band wiring are supposed to give good stability. Here we give an account of our experience with this procedure. Methods: We treated ten patients with comminuted fractures of the olecranon by multiple tension-band wiring and a graft from the iliac crest between 1999 and 2002 at Ayub Teaching Hospital, Abbottabad. After initial immobilization strengthening and endurance exercises were started. The patients were followed up for stability, muscle strength, active range of flexion and extension at elbow and rotation of forearm. Results: The time to union of the fractures was 3 to 7 months. No patient reported difficulties with activities of daily living or symptoms of instability of the elbow. The median flexion was up to 135° (125° to 145°) with a median flexion contracture of 15° (range10° to 30°). The median pronation was 70° (60° to 80°) and median supination 79° (70° to 90°). Only three patients had mild pain and loss of strength. Five patients had excellent and 5 good results with a median Broberg and Morrey index score of 94.5 points (84 to 100). Conclusion: Our results are in accordance with those reported from other centres and the technique is thought to be a practical alternative to plate fixation of olecranon fractures with extreme comminution. Keywords: Olecranon; comminuted fracture; tension band wiring